2021
DOI: 10.1186/s12913-021-06479-0
|View full text |Cite
|
Sign up to set email alerts
|

Perceived consequences of healthcare service decentralization on access, affordability and quality of care in Khartoum locality, Sudan

Abstract: Background Decentralization of healthcare services has been widely utilized, especially in developing countries, to improve the performance of healthcare systems by increasing the access and efficiency of service delivery. Experiences have been variable secondary to disparities in financial and human resources, system capacity and community engagement. Sudan is no exception and understanding the perceived effect of decentralization on access, affordability, and quality of care among stakeholder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Positive effects included reduced medication errors,61 increased screening of pregnant women for HIV,63 high patient satisfaction with the services61 62 64 65 68 and trustful relations between the providers and users 61 62. Negative effects were reduced access and affordability of services and client satisfaction,67 decreased utilisation of services and additional costs incurred in procuring the drugs from private providers 68…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Positive effects included reduced medication errors,61 increased screening of pregnant women for HIV,63 high patient satisfaction with the services61 62 64 65 68 and trustful relations between the providers and users 61 62. Negative effects were reduced access and affordability of services and client satisfaction,67 decreased utilisation of services and additional costs incurred in procuring the drugs from private providers 68…”
Section: Resultsmentioning
confidence: 99%
“…Decentralisation of decision-making, planning and implementation had varied impacts on QoC 65–68. In Sudan, decentralisation resulted in the deterioration of the overall QoC and utilisation of services.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is supported by previous studies which reported that distance to healthcare facilities was a potential barrier to accessing healthcare services in LMICs. 44 , 45 Patients' educational level, employment status and chronic comorbid conditions were also identified as significant determinants influencing their healthcare‐seeking preferences. This may be due to patients with chronic illnesses being more likely to prioritize treatment, management and quality of life over other life choices they may face.…”
Section: Discussionmentioning
confidence: 99%